Application of Taguchi Methods to Investigate Factors Affecting the Kinematic Viscosity of Methyl Ester of Tobacco Seed Oil - Ayhan, Vezir (Asian Journal of Chemistry, 2010)
Vegetable oils and their esters are alternative renewable fuels for compression ignition engines. One of the main difficulties of using vegetable oils as fuel in diesel engines is their high kinematic viscosity. Transesterification appears to be the most promising technique to reduce the viscosity. Reaction temperature, alcohol/oil molar ratio, type and amount of catalyst, reaction duration and the water content in free fatty acid are the most important parameters in biodiesel production by the transesterification method. One of the most important issues in biodiesel is the viscosity and the factors affecting it for achieving EN 14214 standards. In this study, optimum levels of the variables affecting the viscosity of tobacco seed oil methyl ester were determined using Taguchi's technique at 40, 50 and 60 ºC and 1/4, 1/6 and 1/10 of alcohol/oil molar ratios and addition of 0.5, 1.0 and 1.5 % KOH and NaOH catalysts were chosen as parameters. The Taguchi design method revealed that choosing right catalyst, reaction temperature, alcohol/oil molar ratio and catalyst amount are important factors in view of optimization of kinematic viscosity of tobacco seed oil methyl ester.